Is God Morally Indifferent? The Problem of Inference according to David Hume (Diametros, 2018)
The article is devoted to an analysis of David Hume’s position on God’s benevolence in his Dialogues Concerning Natural Religion. The focal point is the problem of inference and the accompanying arguments concerning the relations between good and evil, as well as the four circumstances in which evil enters the world. In the conclusion, I discuss the hypothesis of moral indifference as Hume’s skeptical voice in the debate on the possibility of inferring the moral attributes of God on the basis of experience.
Keywords: the problem of evil; David Hume; the problem of inference; God; the hypothesis of moral indifference